2017
DOI: 10.1055/s-0037-1603934
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Coracoid Bone Graft Placement: Open versus Arthroscopic Latarjet

Abstract: Purpose  The aim of this study was to compare the accuracy of the coracoid bone graft placement with the open Latarjet-Patte and arthroscopic Latarjet (arthro-Latarjet) procedures in the treatment of anterior instability of the shoulder. Methods  Forty-six patients affected by anterior shoulder instability were divided into two groups. In group A ( n  = 25), patients were operated by arthroscopic Latarjet (arthro-Latarjet) procedure and in group B ( n  = 21), patients were operated by open Latarjet-Patte proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
3
24
0
2
Order By: Relevance
“…By comparison, AL had lower accuracy rates across all clusters, reaching a maximum of 78%. The latter finding is similar to the results of a study comparing graft placement accuracy in open Latarjet versus AL 12 ; in that study, 76% of arthroscopic cases had optimal coracoid graft positioning based on postoperative CT scan. It should also be noted that in the same study, open Latarjet cases demonstrated 100% accuracy of graft placement.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…By comparison, AL had lower accuracy rates across all clusters, reaching a maximum of 78%. The latter finding is similar to the results of a study comparing graft placement accuracy in open Latarjet versus AL 12 ; in that study, 76% of arthroscopic cases had optimal coracoid graft positioning based on postoperative CT scan. It should also be noted that in the same study, open Latarjet cases demonstrated 100% accuracy of graft placement.…”
Section: Discussionsupporting
confidence: 86%
“…It should also be noted that in the same study, open Latarjet cases demonstrated 100% accuracy of graft placement. 12 Thus, AAGR preserves the accuracy of graft placement attained with an open procedure while providing the advantages of an arthroscopic approach. However, the factors responsible for difficulties in lower graft positioning for AL are yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Five of the included studies reported on radiographic outcomes. Three of the five studies ( n = 126 arthroscopic, 106 open, p > 0.05) found no significant difference in the coracoid graft positioning between the two techniques [ 13 , 18 , 19 ], one study ( n = 25 arthroscopic, 21 open, p = 0.025) found the arthroscopic technique to be significantly more likely to have ideal graft positioning [ 18 ], and conversely one study ( n = 44 arthroscopic, 46 open, p < 0.001) found the open procedure to be significantly more likely to have ideal graft positioning [ 17 ]. Three of the studies reported on screw divergence angles, two studies ( n = 69 arthroscopic, 67 open, p = 0.10–0.12) found no significant difference between the two techniques [ 17 , 18 ], and one study ( n = 28 arthroscopic, 36 open, p = 0.017) found the open technique to have significantly less rates of excessively (> 10°) divergent screws [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…25 27 28 Ainda assim, existem estudos que demonstram que o posicionamento do enxerto na cirurgia artroscópica pode ser desafiador, assim como o ângulo adequado dos parafusos. 29 30…”
Section: Discussionunclassified